PERANCANGAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU DI SDN 205 KOTA JAMBI BERBASIS WEB - Dona Primayu Ekarsih; M. Dimas Ramadhan; Peri Sandiko Saputra; Dodo Zaenal Abidin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Education is a planned system to create a learning atmosphere and learning or training process so that students can actively develop their potential. Along with the rapid development of information systems, of course it can help an institution to support and make it easier to achieve the targets and goals of the educational institution itself. But of course the use of technology must be based on a structured system so that the problem in a case can be broken down into sub-systems/parts/components that are interrelated with one another and related to achieving a certain goal. A website-based registration information system for prospective new students, is a registration system for prospective new students who want to register to school through website media, without having to come directly to school, so that it will make it easier for prospective new students to carry out the registration process, so that it will save more time and effort and can minimize the registration queue process at school. From these problems a web-based new student admission application is needed so that it can facilitate the committee in the process of registering and storing data on prospective new students, for prospective students it is hoped that it will be easier to carry out the registration process and faster to get information about the school.